2023
DOI: 10.1371/journal.pgen.1010781
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping functions of SIX homeoproteins during embryonic myogenesis

Abstract: Four SIX homeoproteins display a combinatorial expression throughout embryonic developmental myogenesis and they modulate the expression of the myogenic regulatory factors. Here, we provide a deep characterization of their role in distinct mouse developmental territories. We showed, at the hypaxial level, that the Six1:Six4 double knockout (dKO) somitic precursor cells adopt a smooth muscle fate and lose their myogenic identity. At the epaxial level, we demonstrated by the analysis of Six quadruple KO (qKO) em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 106 publications
0
0
0
Order By: Relevance
“…In contrast, craniofacial muscles such as EOMs, facial, mastication and subsets of neck muscles, are derived from cranial mesoderm and do not express Pax3 [2,6,18,19]. The early head mesoderm harbors instead a complementary set of upstream markers including Tbx1, Pitx2 and the Six gene family [20][21][22][23]. Notably, Tbx1 (T-Box Transcription Factor 1), is an upstream regulator for the facial, jaw, neck, laryngeal and esophagus muscles, but not of the EOMs [18,20,21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, craniofacial muscles such as EOMs, facial, mastication and subsets of neck muscles, are derived from cranial mesoderm and do not express Pax3 [2,6,18,19]. The early head mesoderm harbors instead a complementary set of upstream markers including Tbx1, Pitx2 and the Six gene family [20][21][22][23]. Notably, Tbx1 (T-Box Transcription Factor 1), is an upstream regulator for the facial, jaw, neck, laryngeal and esophagus muscles, but not of the EOMs [18,20,21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms that govern the emergence and maintenance of cranial myogenic cells are poorly understood. As Pax3 is absent in the EOMs, and Pax7 is expressed after the MRFs [32,33], it is possible that Pitx2 or other transcription factors such as the Six family members [22,34] specify the Pax7 + population in this location. Yet, as no MuSC lineage-specific deletion of Pitx2 has been performed in EOMs, it is unclear: i) to what extent Pitx2 is required temporally for emergence and maintenance of the MuSC population, and its relative function compared to the MRFs and Pax7; ii) if Pitx2 is continuously required for maintenance of the adult MuSC population.…”
Section: Introductionmentioning
confidence: 99%
“…population in the EOMs requires further investigation. Moreover, a recent study showed that Six1 and Six2 genes are required for craniofacial myogenesis by controlling the engagement of unsegmented cranial paraxial mesodermal cells in the myogenic pathway [22]. It remains unclear if expression of these genes in adult MuSCs would be required for Pax7 maintenance in the EOMs.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In contrast, craniofacial muscles such as EOMs, facial, mastication and subsets of neck muscles, are derived from cranial mesoderm and do not express Pax3 [2,6,18,19]. The early head mesoderm harbors instead a complementary set of upstream markers including Tbx1, Pitx2 and the Six gene family [20][21][22][23]. Notably, Tbx1 (T-Box Transcription Factor 1), is an upstream regulator for the facial, jaw, neck, laryngeal and esophagus muscles, but not of the EOMs [18,20,21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation